👤

Oblicz:
a) (1 1/3) do potęgi -3
b) (-2) do potęgi -3
c) 4 do potęgi -2
d) (0,2) do potęgi -4
e) (0,1) do potęgi -1


Odpowiedź :

Odpowiedź:

[tex] {(1 \frac{1}{3}) }^{ - 3} = {( \frac{4}{3} )}^{ - 3} = {( \frac{3}{4} )}^{3} = \frac{27}{64} [/tex]

[tex] {( - 2)}^{ - 3} = {( - \frac{1}{2}) }^{ 3} = - \frac{1}{8} [/tex]

[tex] {4}^{ - 2} = {( \frac{1}{4} )}^{2} = \frac{1}{16} [/tex]

[tex] {(0.2)}^{ - 4} = {( \frac{1}{5}) }^{ - 4} = {( \frac{5}{1} )}^{4} = {5}^{4} = 625[/tex]

[tex] {(0.1)}^{ - 1} = {( \frac{1}{10}) }^{ - 1} = 10[/tex]